2021
DOI: 10.1016/j.ejphar.2020.173620
|View full text |Cite
|
Sign up to set email alerts
|

Targeting pivotal inflammatory pathways in COVID-19: A mechanistic review

Abstract: As an emerging global health crisis, coronavirus disease 2019 (COVID-19) has been labeled a worldwide pandemic. Growing evidence is revealing further pathophysiological mechanisms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Amongst these dysregulated pathways inflammation seems to play a more critical role toward COVID-19 complications. In the present study, precise inflammatory pathways triggered by SARS-CoV-2, along with potential therapeutic candidates have been discussed. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 165 publications
(187 reference statements)
0
29
0
Order By: Relevance
“…Acute, short-term psychosocial stress can also mobilize endogenous factors such as secreted Ly-6/uPAR related protein-1 (SLURP1) that neutralize the infection-promoting effects of nicotine on its receptors by stabilizing barrier function and promoting T-cell activation ( Campbell et al, 2019 ; Peters et al, 2014 M; Razani-Boroujerdi et al, 2004 ; Tjiu et al, 2011 ). Finally, acute psychosocial stress leads to the rapid but transient release of neuropeptides such as SP from peripheral nerve endings in mucosae and skin, and this may contribute to first-line anti-viral defense by short-term upregulation of toll-like receptors (TLRs) ( Larsson et al, 2018 ; Yarmohammadi et al, 2021 ).…”
Section: Which Stress-reducing Interventions May Be Suitable To Prevementioning
confidence: 99%
“…Acute, short-term psychosocial stress can also mobilize endogenous factors such as secreted Ly-6/uPAR related protein-1 (SLURP1) that neutralize the infection-promoting effects of nicotine on its receptors by stabilizing barrier function and promoting T-cell activation ( Campbell et al, 2019 ; Peters et al, 2014 M; Razani-Boroujerdi et al, 2004 ; Tjiu et al, 2011 ). Finally, acute psychosocial stress leads to the rapid but transient release of neuropeptides such as SP from peripheral nerve endings in mucosae and skin, and this may contribute to first-line anti-viral defense by short-term upregulation of toll-like receptors (TLRs) ( Larsson et al, 2018 ; Yarmohammadi et al, 2021 ).…”
Section: Which Stress-reducing Interventions May Be Suitable To Prevementioning
confidence: 99%
“…It also inhibits neuroapoptosis by reducing FGF-2 and suppressing NF-κB ( Xu et al, 2018 ). Considering the critical role of the aforementioned inflammatory mediators in COVID-19 ( Yarmohammadi et al, 2020 ), resveratrol could potentially decline neuroinflammatory signs of COVID-19 patients ( Chen et al, 2005 ). As a major natural derivative of resveratrol, polydatin potentially decline the neural levels of NF-κB, TNF-α, IL-1β, IL-6, IL-8, prostaglandin E2 (PGE2), NO, COX-2, iNOS, matrix metalloproteinase (MMP)-3 and MMP-9, thereby could be a novel agents in combating neuronal inflammatory manifestation in COVID-19 ( Lo Muzio et al, 2020 ).…”
Section: Potential Of Phytochemicals Against Covid-19 Neurological Asmentioning
confidence: 99%
“…As a critical sign of COVID-19, neuroinflammation occurs through elevated levels of neuronal interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, tumor necrosis factor-α (TNF-α), interferon-gamma (IFN-γ), granulocyte colony-stimulating factor (GMCSF), IFN-γ-induced protein 10 (IP-10), monocyte chemoattractant protein-1 (MCP1), macrophage inflammatory protein 1α (MIP1α), and T cell expression ( Xu et al, 2005 ; Yarmohammadi et al, 2020 ). The coronaviruses release inflammatory mediators to stimulate macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent investigations have demonstrated elevated levels of pro-in ammatory cytokines in the critically ill COVID-19 patients compared with moderately ill ones (3,4). Induction of immune responses during the course of COVID-19 has been shown to result in the overproduction of enormous quantities of in ammatory proteins, eventually leading to organ damage (5). Up-regulation of pro-in ammatory cytokines such as IL-6, IL-1β, IL-18, and TNF-α in addition to their downstream molecules have been reported in these patients (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dysregulation of a number of other in ammatory molecules such as IL-2, IL-7, IL-10 and IFN-γ have been associated with COVID-19 (8). Totally, many studies have shown the important impact of IL-6, IFN-γ and TNF-α in the pathobiology of this condition and related organ damage (5). Thus, identi cation of these in ammatory reactions has signi cance in the treatment of patients with COVID-19 infection (9).…”
Section: Introductionmentioning
confidence: 99%